Application of NIR and MIR spectroscopy to assess freshness in sea bream (Sparus auratus) and salmon (Salmo salar) during ice storage - C. Alamprese; N. Sinelli; E. Casiraghi; C. Pompei; F. Rauzzino (International Council of Near Infrared Spectroscopy (ICNIRS), 2012)
Introduction: Modifications that take place in fish muscle post mortem have a significant impact on the aquaculture industry due to their effects on fish quality and consumer acceptance. Storage in ice is widely used, even if a progressive deterioration in sensory and other properties still occurs, mainly due to changes in lipids and proteins. Although a variety of biochemical, physical, and microbiological methods have been used to assess fish freshness, sensory evaluation is still the most satisfactory. However, this approach is time-consuming and not readily available in all situations. The aim of this work was to evaluate the applicability of NIR and MIR spectroscopy to rapidly assess freshness of sea bream and salmon during ice storage. Materials and Methods: Aquacultured ungutted sea breams (Sparus auratus) and gutted salmons (Salmo salar) were obtained 4 days after slaughter, packaged in polystyrene boxes, covered with a layer of flake ice. The samples were stored in ice in a cold room as whole or as fillets, up to 21 and 17 days, respectively. At regular intervals, samples were analyzed by both chemical methods (total volatile basic nitrogen content, thiobarbituric acid reactive substances, trimethylamine level) and spectroscopic techniques (FT-NIR, 12500-3750 cm-1; FT-IR, 4000-700 cm-1). Results and Discussion: Increasing values of the chemical parameters were observed as a function of fish storage time. The PCA analysis of NIR and MIR spectra of both whole fish and fillets reflected the evolution of the chemical parameters, related to storage time. The NIR and MIR spectra discriminated the samples mainly on the basis of lipid oxidation and protein degradation. Conclusion: Results suggested that spectroscopic techniques could be useful tools for a rapid and easy evaluation of fish freshness during storage in ice. This approach proved viable in particular for sea bream and for fish fillets. Novelty statement: NIR and MIR spectroscopy could enable rapid, non-intrusive, and low-cost measurement of fish ...